2022
DOI: 10.3390/ijerph192416878
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study Comparing Mental Health Outcomes in Frontline Emergency Department Healthcare Workers through the Different Waves of the COVID-19 Pandemic

Abstract: As countries transition from the COVID-19 pandemic to endemic status, healthcare systems continue to be under pressure. We aimed to quantify changes in depression, anxiety, stress and post-traumatic stress disorder (PTSD) between 3 cohorts (2020, 2021 and 2022) of our Emergency Department (ED) healthcare workers (HCWs) and those who had worked through all 3 phases of the pandemic; and identify factors associated with poorer mental health outcomes (MHOs). In this longitudinal single-centre study in Singapore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Some other longitudinal studies have also reported persistent mental health impacts on frontline healthcare workers despite changes in, and subsidence of, pandemic waves. 4,13,14 In contrast, others have found variation in healthcare worker wellbeing over the duration of the pandemic. A recent Australian study reported a slight improvement in healthcare worker wellbeing after the initial 2 years 18 and a study in the UK found the proportion of healthcare workers reporting common mental disorders was greater during periods when demands on the healthcare system increased due to factors such as higher COVID-19 case numbers and associated staff shortages.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Some other longitudinal studies have also reported persistent mental health impacts on frontline healthcare workers despite changes in, and subsidence of, pandemic waves. 4,13,14 In contrast, others have found variation in healthcare worker wellbeing over the duration of the pandemic. A recent Australian study reported a slight improvement in healthcare worker wellbeing after the initial 2 years 18 and a study in the UK found the proportion of healthcare workers reporting common mental disorders was greater during periods when demands on the healthcare system increased due to factors such as higher COVID-19 case numbers and associated staff shortages.…”
Section: Discussionmentioning
confidence: 95%
“…[10][11][12][13] Few have collected data over a longer time period, and these have mostly focused on a particular group of healthcare workers. 4,[14][15][16] These studies suggest that healthcare workers have experienced psychological distress at various timepoints during the COVID-19 pandemic 4,10,11,13 and their wellbeing deteriorated as the pandemic continued. 10,[13][14][15] Although these studies provide important evidence about the immediate impact of the pandemic on healthcare workers, little is known about the longer-term impacts.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Risikofaktoren für einen schweren COVID- 19 VondenBefragtengaben67 %einmoderates oder hohes Level an psychologischem Stress an [11]. Eine Studie aus Singapur belegt eine Zunahme der Prävalenz depressiver Veränderungen, Stress und Angst bei Mitarbeitern in Notaufnahmen mit zunehmender Dauer der Pandemie [39]. Alarmierende Daten zu Burn-out-Raten bei Angestellten im Gesundheitssystem werden aber ebenso aus Europa berichtet [9,41].…”
Section: Covid-19-risiko Bei Chronischentzündlichen Darmerkrankungenunclassified
“…This finding suggests that the burden for the hospitals during the COVID-19 pandemic had a long-term impact on HCWs' emotional distress. Previous longitudinal studies have shown that HCWs have experienced high levels of anxiety, depression, burnout, and posttraumatic stress disorder (PTSD) as a result of their work during the pandemic [42][43][44]. The prolonged nature of the pandemic, as well as long working hours, exposure to critically ill patients, and the risk of contracting the virus itself, added to the stress and emotional toll on HCWs [45].…”
Section: Predicting Depressive and Anxiety Symptoms At Follow-upmentioning
confidence: 99%